Record of sun coral (Tubastraea spp.) polyps attached to Parribacus antarcticus on the South Atlantic coast of Brazil (~8S) - Nykon Craveiro; Davy Barbosa Bérgamo; Roberto Correia Moretti; Andressa Montebello Sales; José Souto Rosa Filho (PANGAEA, 2024)
This video shows the sun coral (Tubastraea spp.) attached to the carapace of an adult a sculptured slipper lobster (Parribacus antarcticus). This recording was made with an underwater camera during a technical dive, in the mooring dolphins (8°23 extquotesingle55.445S 34°57 extquotesingle12.435W), at a depth of 7 meters on June 28, 2023 in Suape Harbor, Pernambuco, off the northeast coast of Brazil. The dive was being carried out to inspect the mooring dolphins and, during the inspection, the lobster with the sun coral polyps on its carapace was observed. The sun coral is an invasive species that can have a serious impact on native biota, and the record of its occurrence in a mobile organism is unique, which implies the need to include the inspection of live animals in monitoring protocols.